2019
DOI: 10.1021/acs.bioconjchem.9b00295
|View full text |Cite
|
Sign up to set email alerts
|

Triazine-Modified 7-Deaza-2′-deoxyadenosines: Better Suited for Bioorthogonal Labeling of DNA by PCR than 2′-Deoxyuridines

Abstract: 6-Ethynyl-1,2,4-triazine is a small bioorthogonally reactive group we applied for fluorescent labeling of oligonucleotides by Diels–Alder reactions with inverse electron demand. We synthetically attached this functional group to the 7-position of 7-deaza-2′-deoxyadenosine triphosphate and to the 5-position of 2′-deoxyuridine triphosphate. Both modified nucleotide triphosphates were used in comparison for primer extension experiments (PEX) and PCR amplification to finally yield multilabeled oligonucleotides by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Although 119b was much more synthetically available, 119c was found to be better suited for DNA polymerase-based oligonucleotide preparations (Scheme 37b). 150 Furthermore, oligonucleotides 120b attached with two bioorthogonally reactive groups (1-methylcyclopropene and 1,2,4-triazine) could be obtained via a sequential DNA polymerases technique. Dual labeling with two different fluorescent dyes (BCN-rhodamine and tetrazine derivative 122a) was found to be not only bioorthogonal in general but also mutually orthogonal (Scheme 37c).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although 119b was much more synthetically available, 119c was found to be better suited for DNA polymerase-based oligonucleotide preparations (Scheme 37b). 150 Furthermore, oligonucleotides 120b attached with two bioorthogonally reactive groups (1-methylcyclopropene and 1,2,4-triazine) could be obtained via a sequential DNA polymerases technique. Dual labeling with two different fluorescent dyes (BCN-rhodamine and tetrazine derivative 122a) was found to be not only bioorthogonal in general but also mutually orthogonal (Scheme 37c).…”
Section: Introductionmentioning
confidence: 81%
“…174 In contrast to the concerted mechanism for the conventional IEDDA reactions, this reaction was postulated to proceed via a stepwise pathway. In the presence of base, the nucleophilic addition of activated acetonitriles 148 or ketones 150 Although the normal IEDDA reactions of 1,2,3-triazines prefer to proceed via the C4/N1 (C6/N3) mode, the cycloaddition pattern could be tuned to C5/N2 mode in some cases. In 2014, Boger and co-workers disclosed the C5/N2mode IEDDA reaction for the synthesis of pyridazines (Scheme 48).…”
Section: Ring-expansionmentioning
confidence: 99%
“…This property was used to create another level of orthogonality for nucleic acid labeling (Figure ). Our group managed to incorporate the 1,2,4-triazine-modified nucleotides 57 – 59 enzymatically into DNA and labeled them by BCN-modified dyes as reactive partners. , The dUTP-derived building block 58 was just hardly tolerated by the DNA polymerases, while the 7-deaza-2′-deoxyadenosine derivative 59 apparently was much better suited for enzymatic DNA preparation, making its tough synthetic accessibility worth it.…”
Section: Postsynthetic Labeling Of Synthetic Dna and Rnamentioning
confidence: 99%
“…The 6-ethynyl-1,2,4triazine modification is much better tolerated by the KlenTaq DNA polymerase when attached to 7-position of the triphosphate of 7-deaza-2′-deoxyadenosine 59 than to the 5position of 2′-deoxyuridine 58 according to PAGE analysis of PCR products and real-time kinetic analysis of DNA polymerase activity during PEX on biosensors. 125 Such intriguing results were obtained also by PEX experiments using the 1-methylcyclopropene-modified building blocks 76 and 77 for a variety of different DNA polymerases (Hemo KlenTaq Vent (exo-) and Deep Vent (exo-). 158 The elongation products were labeled in vitro by 1,2,4,5-tetrazine-modified TAMRA dyes (90% yield after 2 h).…”
Section: Bioconjugate Chemistrymentioning
confidence: 99%
“…[136] Recently, the method was successfully used in the DNA labeling. [137] In 2019, Boger's group reported the synthesis, characterization, and cycloaddition reactivity of a monocyclic aromatic 1,2,3,5-tetrazine and found that it showed good stability and rapid IEDDA rate with electron-rich or strain-containing dienophiles. [138] In addition, Murphy and Houk reported the cycloaddition reactions of tetrachlorocyclopentadiene ketal (142) with bicyclononyne (BCN) (85) or trans-cyclooctene (TCO) for bioorthogonal labeling (Figure 30).…”
Section: Inverse Electron Demand [4 + 2] Cycloadditions Leading To Bi...mentioning
confidence: 99%